Malong : the magic cloth - Ordinario, Mary Ann A.; Atienza, Pepot Z. (Kidapawan City : ABC Educational Development Center, 2016)
What makes the malong so special? Find out the mystery of the magic cloth as a little boy tells his true-to-life exceptional journey with his family. Children carry a little bit of enchantment all the time. This is the ultimate book for them to discover the magical things around them.
International Children's Content Right's Fair for ASEAN Children's Book Illustrator, 2017.
International Children's Content Right's Fair for ASEAN Children's Best in Fiction, 2017.
Keywords: Manners and customs -- Juvenile fiction